Free-recall retrieval practice tasks for students with ADHD: whole-text versus section recall - Stern, Pnina; Halamish, Vered (Frontiers in Psychology, 2023)
Introduction The present study examined the relative effectiveness of two free-recall-based retrieval practice methods for text learning among students with ADHD. Method Participants with and without ADHD read texts and practiced them by freely recalling the information either after reading each section or after reading the whole text. Two days later, participants completed a free-recall criterion test on the texts. Results The results suggested that although more idea units were recalled during practice in the section recall condition than in the whole-text recall condition, the whole-text recall condition outperformed the section recall condition on the criterion test in terms of the proportion of idea units recalled, although neither retrieval practice conditions outperformed restudying. These findings were obtained for both groups. Exploratory analyses further demonstrated a benefit of the whole-text over section recall also in terms of the order in which idea unites were recalled and suggested that the recall of ADHD participants was less well ordered compared with participants without ADHD. Discussion Based on these findings, when using retrieval practice, whole-text free-recall can be recommended for students with ADHD, along with implementing strategies to enhance the mental organization of the studied materials.